Kapabilitas Sebagai Mediasi Kualitas Sumber Daya Manusia dan Inovasi terhadap Kinerja Karyawan Mebel Jepara - Elysia Salsabila; Eko Nur Fuad (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the role of capabilities as a mediator between the influence of human resource quality and innovation on employee performance in the Jepara furniture industry. The research approach used was quantitative with explanatory methods, involving 100 permanent employees of a medium-sized furniture company in Jepara Regency as respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to test direct and mediation relationships between variables. The results indicate that human resource quality and innovation have a significant positive effect on employee performance, and both also have a positive effect on employee capabilities. Furthermore, capabilities were shown to mediate the relationship between human resource quality and innovation on employee performance, strengthening their influence on individual performance. The control variable of length of service also had a positive effect, while job position had no significant effect. These findings confirm that employee capability development is key to improving work effectiveness and competitiveness in Jepara furniture companies.   Keywords: Human Resource Quality, Innovation, Capability, Employee Performance